The effect of different temperature on vital characters of Aphidius matricariae ( Haliday ) - Raad H. Awad; Juhaina I. Mohammed (مجلة جامعة الانبار للعلوم الصرفة, 2015)
The study showed that the temperature impact on some of the vital qualities of an intruder Aphidius matricariae when his breeding at different temperatures ,As the results of the study showed that the treatment of thermal 20 C outperformed morally and gave the highest number of mummies extent of 37-45 and an average of 42.33 ± 4.16 mummy.Followed by treatment of spam raising the temperature 30 C the number of mummies given the extent of 11-14 and an average 12.33 ± 1.52 mummy .While at breeding this Parasites thermal 10 C gave the least number of mummies and reached long- 1-3 and an average 2 ± 1 mummy . And an average of 18.88 in the recipetically .And that the temperature effect on the proportion of the eggs to hatch as thermal treatment 20C given higher proportion of hatching the extent of 74-90 and an average of 84.66 ± 9.23 hatch eggs Excelled morally so the rest of the transactions , followed by treatment of spam raising the thermal 30 C extent of 36-46 and an average of 40.66 ± 5.03 hatched egg , while recorded the treatment 10C lowest percentage for the eggs to hatch since given the extent of 10-30 and an average of 20 ± 10 and reached overall average of 48.44 egg recipe.